Spatio-temporal propagation of cascading overload failures in spatially embedded networks - Jichang Zhao (Nature Portfolio, 2016)
Overload failures propagate through hidden functional dependencies across networked systems. Here, the authors study the spatio-temporal propagation behaviour of cascading overload failures, and find that they spread radially from their origin with an approximately constant velocity.